Peningkatan Motivasi Dan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Co-Op Co-Op - Indayani, Mawar; Mursalin, Enggal (Biosel Biology Science and Education, 2022)
Biology learning carried out at SMPN 1 Air Buaya is indicated to be less effective because it is still teacher centered learning. This is indicated by the low motivation and student learning outcomes. One of the student-centered cooperative learning models is the co-op co-op type of learning model. This classroom action research aims to improve the motivation and learning outcomes of class VIII students through the application of the co-op co-op learning model on the respiratory system material in humans. This research is carried out in 2 cycles, where each cycle goes through the stages of planning, implementing, observing, and reflecting. The results showed that the co-op co-op learning model was able to improve student learning outcomes, namely as many as 89.4% of students and the average achievement of student motivation was 82.7%. Referring to the results of the study, classroom teachers should be more intensive in applying the co-op co-op learning model to other biology learning subjects. Keywords: co-op co-op, biology learning, motivation, learning outcomes